Plate Heat Exchanger Efficiency - Kamarulzaman, Muhamad Redza; Sies, Mohamad Farid (Research Progress in Mechanical and Manufacturing Engineering, 2025)
The research project to find the efficiency of the model plate heat exchanger. Plate heat exchanger with the flowrate of co-current and counter current. The study analyze between hot water constant and cold water constant of the power lost, efficiency, LMTD and the heat transfer coefficient. Experiment with an experimental heat exchanger model under different flow rates for the hot and cold water (2LPM, 4LPM, 6LPM, 8LPM, 10LPM) .The key parameter are the water flow rates and temperature. The study maintaining hot water and cold water constant flow rate (7.5LPM), reveal that the efficiency for the counter current drop as the flow rates increases. The co-current flow especially the hot water constant shows that the efficiency is increasing stable showing a stable plate heat exchanger compare to counter current flow